Uncertainty and the market valuation of R&D within a real options logic - Oriani, Raffaele; Sobrero, Maurizio (Strategic Management Journal, 2008)
Abstract The aim of this study is to provide new theoretical insights and empirical evidence on the effect of market and technological uncertainty on the market valuation of a firm's R&D capital. A set of hypotheses is developed adopting a real options logic and tested on a panel dataset of 290 manufacturing firms traded in the UK. Consistently with our theoretical model, we show that market and technological uncertainty have distinct effects on the valuation of R&D investments. The results have several important implications for resource allocation to R&D under uncertainty, which we discuss in the concluding section. Copyright © 2008 John Wiley & Sons, Ltd.